Crystal structure determination of anti‐DNA Fab A52. Issue 8 (18th February 2014) - Stanfield, Robyn L.; Eilat, Dan
ABSTRACT A52 is a murine monoclonal antibody isolated from autoimmune New Zealand Black/New Zealand White F1 mice that recognizes single and double stranded DNA. This mouse strain spontaneously develops systemic lupus erythematosus‐like symptoms and has served as a model for that disease for many years. The 1.62 Å crystal structure of the A52 Fab fragment reveals an H3 complementarity determining region with four closely spaced arginine residues, creating a positively charged surface to accommodate bound DNA. Proteins 2014; 82:1674–1678. © 2014 Wiley Periodicals, Inc.